Community participation in five selected public health research projects Iran - Nejad, Nasrin Bahrami (2012)
Community participation in public health research through developing the Community Based Participatory Research (CBPR) project is an essential strategy for addressing contemporary health challenges in all communities. However, the application of community participation in CBPR has encountered many challenges especially in developing countries. Community participation is a complex concept that has little consensus regarding its process, especially in CBPR approach. A qualitative research paradigm using the grounded theory approach was conducted to explore and understand the community participation within the context of public health projects based on CBPR in order to develop substantive theory to explain community participation in CBPR projects. This study specifically has explored how was community participation perceived by stakeholders involved in public health project based on CBPR? And what were the contextual conditions that affected their participation in public health project based on CBPR? Thirty-nine respondents including community members, representatives from social organizations, academic researchers, and other health care providers involved in public health research projects based on CBPR in Iran were interviewed in depth. Research memos formed other sources of data. Each interview was tape recorded, transcribed verbatim and analysed according to the constant comparative method through open, axial, and selective coding. Trustworthiness was established through member checks, source triangulation, peers examination, reflexivity and an audit trail of the research activities. The result of the study indicated that community participation in CBPR project is an interactive process that is shaped between community members and professional stakeholders in the public health care system and social context.‘Congruence of Stakeholders’ emerged as the core participation process. The core participation process consists of three levels of participation, namely ‘engaging’, ‘sharing’ and ‘collaborating’. The level of participation was affected by intervening and contextual conditions which include affective response, cooperative environment, readiness, and right. These contextual conditions affected the interaction between stakeholders, as well as the level of the stakeholder’s participation. The findings showed that achieving the optimal levels of participation depend on the cooperative environment. The cooperative atmosphere is defined by recognition, communication, and consistency. During the process of participation, the relationship between stakeholders was influenced by the affective response between them. Such response is characterized by sensitiveness, trust, and respectfulness. According to the results of this study, the willingness to participate required a certain readiness at the individuals and organizational levels. At the individual level, readiness needs the motivation and capacity of stakeholders. Readiness at the organizational level relied on the structure, valuing system, and organizational stability of the public health care system and other related social organizations. The impact of political and social environments on community participation was reflected by the concept of right. Ensuring the right for participation required a call for community voice in public health issues and accountability on the part of professional stakeholders and government. The findings of this study provided policy makers and health care providers with new knowledge regarding community participation in the public health context in Iran.